Costs and benefits of new apprenticeships - Dockery, Alfred Michael; Stromback, Carl; Kelly, R.; Norris, K. (National Institute of Labour Studies, 2001)
The introduction of New Apprenticeships in January of 1998 marked an important initiative in Australia's efforts to develop a more encompassing system of employment based vocational education and training. This paper draws on evidence from case studies of 60 employers to assess the impact of these reforms on training outcomes and practices. The provisions most enthusiastically embraced by employers include competency-based assessment and flexibility in time spent in training. However, these positive indicators of the reform process have not translated into an improved cost/benefit outcome for employers. Comparison with previous findings suggests that the net cost of employing trainees has not really changed while the net cost of apprentices is estimated to be higher than it was in 1996.